The characterization of the cells involved in the mixed leukocyte reaction in the rabbit and its relation to allograft rejection. - Milthorp, Peter. (University of Ottawa (Canada), 1979)
The rabbit mixed leukocyte reaction (MLR) was systematically investigated in terms of the properties of the stimulator and responder cells. It was demonstrated that culturing the cells in medium RPMI-1640, supplemented with complement inactivated rabbit serum (final concentration 2.5%), for five days at 37°C, in a humidified atmosphere of air:CO2 (95:5) provided the optimal condition for the blastogenic response (3H-thymidine incorporation) of cells in the MLR. The cells of the Peyer's patches and the mesenteric lymph nodes responded to the greatest extent in the MLR. Thymus and bone marrow cells cultured individually or in combination did not respond. The cells of the Peyer's patches, spleen and mesenteric lymph nodes were the most potent stimulating cells. There was no correlation between stimulating capacity and the percentage of stimulator cells bearing surface immunoglobulins. Whole body irradiation of normal adult rabbits with doses of 600R or more resulted in the consistent elimination of the MLR responder cell activity in the immediate post irradiation period (1 to 2 days). There was no evidence of any preferential recovery of MLR responder activity by cells in any of the different lymphoid organs. The cells of skin allografted rabbits, following rejection of the allografts, showed accelerated one-way MLR responses specific to stimulator cells from the allograft donors.
Keywords: Agriculture, Animal Pathology.